REASSESSING THE LINKAGES AMONG ENTREPRENEURSHIP, INSTITUTIONS AND GROWTH - Tebaldi, Edinaldo (2024)
Abstract   This article examines the role of institutions and entrepreneurship to foster economic development under increasing complex economic structures caused by structural changes. The empirical work utilizes data from several sources including the Penn World Table 9.1, The Global Entrepreneurship and Development Institute, the Observatory of Economic Complexity (OEC) at the MIT, and The International Country Risk Guide (ICRG). The empirical work circumvents the endogeneity and heterogeneity problem that plague cross-country regressions by using the Arellano and Bover (1995) and Blundell and Bond (1998) system GMM estimator. The results show that while entrepreneurship is positively correlated to economic development, this correlation disappears when controlling for heterogeneity and/or for differences in quality of institutions. There is also evidence that the importance of institutional quality for economic development increases when an economy become more complex. Overall, findings of this research suggest that quality of institutions is not only important to foster entrepreneurship, but also very important to mediate complex economic structures that emerge as part the development process and structural changes. The main policy implication of this work is that economies in transition must take steps to improve the quality of their institutions, particularly of institutions that enable productive entrepreneurship and mediate the increased complexity resulting from the inherent structural transformation associated with economic development. JEL Codes: O57, O43, O47